Redefining Creativity and Well-being: A Feasibility Study for a New Course at a Small Liberal Arts College in Japan - Lee Friederich; Yuko Taniguchi; Naoko Araki; Naeko Naganuma; Joel Friederich; Kathryn R. Cullen (Creative Arts in Education and Therapy)
Considering the escalating mental health needs of college students and the stigma surrounding mental illness in Japan, this study explores how creativity impacts student well-being. Eleven students enrolled in an intensive 2-week course participated in the study, completing the Comprehensive Inventory of Thriving (CIT) and post-course interviews. Total CIT scores increased significantly from pre- to post-course (p=0.04). Post-course interviews suggested eight themes, three of which are explored here: safe spaces, redefining creativity, and self-acceptance and self-compassion. The article includes a case study of one student’s learning journey to synthesize quantitative and qualitative findings. This preliminary study finds that creative activities, combined with learning in positive psychology, can help college-level students in Japan achieve a greater sense of well-being.